Sport and physical education in Germany - Naul, Roland; Hardman, Ken, 1938-; International Society for Comparative Physical Education and Sport (London ; New York : Routledge, 2002)
Sport and physical education represent important components of German national life, from school and community participation, to elite, international level sport. This unique and comprehensive collection brings together material from leading German scholars to examine the role of sport and PE in Germany from a range of historical and contemporary perspectives. Key topics include:* sport and PE in pre-war, post war and re-unified Germany* sport and PE in schools* coach education* elite sport and sport science* women and sport* sport and recreation facilities. This book offers an illuminating insi.
Context for sport and physical education in Germany / Ken Hardman -- History of sport and physical education in Germany, 1800-1945 / Roland Naul -- Sport and physical education in the two Germanies, 1945-1990 / Ken Hardman and Roland Naul -- Sports and physical education in re-unified Germany, 1990-2000 / Roland Naul and Ken Hardman -- Physical education in schools / Roland Naul -- Physical education teacher training / Roland Naul -- Coach education and training / Arnd Kruger -- Elite sport / Martin-Peter Buch -- Sport for all system and policy / Ilse Hartmann-Tews -- Sport for women / Gertrud Pfister -- Sport facilities / Friedler Roskam.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Sports -- Germany -- History; Physical education and training -- Germany -- History; Sports -- Allemagne -- Histoire; Éducation physique -- Allemagne -- Histoire; SPORTS & RECREATION -- History; Physical education and training; Sports; Germany; Electronic books; History